Manfaat Implementasi TKDN pada Pengadaan Barang/Jasa Sektor Hulu Migas - Ika Puspita Nur Aini; Ervina Loide Hutasoit; Sarjuni Adicahya; Sandry Pasambuna; Yeni Ernawati (Ikatan Ahli Pengadaan Indonesia (IAPI), 2025)
The Domestic Component Level (TKDN) policy is a strategic instrument implemented by the Indonesian government to increase the use of local products and services across various industrial sectors, particularly in the upstream oil and gas sector. This study aims to examine the benefits of TKDN implementation in procurement within the upstream oil and gas industry and to assess its effectiveness in promoting national industrial self-reliance. Using a qualitative and descriptive approach through literature review, the research finds that the oil and gas sector demonstrates the most comprehensive achievement in the implementation of the TKDN policy. Although the TKDN realization in 2024 reached 58.36%, which is still below the set target, there is a consistent upward trend year by year. The policy has proven effective in boosting investment realization, strengthening the capacity of local industries, and increasing domestic employment. Nevertheless, several challenges still hinder optimal outcomes, such as limited domestic production capacity and the low competitiveness of local products. This study concludes that the success of TKDN implementation heavily relies on the synergy between government policies, industrial readiness, and the commitment of stakeholders.